The ANALYSIS OF HEAD LOSSES AND EFFICIENCY OF CENTRIFUGAL PUMP G31-41A PLANT 35 AT PT. PERTAMINA REFINERY RU V BALIKPAPAN (Teknosia, 2024)
In the oil processing and manufacturing industry (PLTGU) in Indonesia, including PT.PERTAMINA. Where the processing is in the form of crude oil, BBM (fuel oil). Non-Fuel, Petrochemicals and oil and gas supplies, for the eastern part of Indonesia. One of the main ingredients of this processing is water (H2O). Therefore, the location or location of industrial plants must be close to raw water sources, namely sea water or the need for clean watercontinuously andmaintained. Because the need forwateris very large, the flowof wateris madeaccording to the needs by building a pumping station. The water needed for cooling water is then channeled to the main reservoir for raw materials for making oil. Pumps are used as atool to move fluids from one place to another through pipe media with changes in pressure on the fluid. Pumps are usually for liquids. In the pump installation from the cooling tower installation to the main reservoir is the Vogel centrifugal pump, where the head loss on the suction pipe line is 0.8993 m, the head loss for the outlet pipe line is 1.211 m with a total head loss of 0.825 m and the efficiency or performance of the pump G-31-41A centrifuge of 33.78%